MEMBER SAVINGS AND NON-PERFORMING LOANS' EFFECT ON BUSINESS CAPITAL PERFORMANCE - Syamsu Rijal; Eddy Silamat; Sri Dewi Yusuf; Ariawan Ariawan (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the effect of members' savings and non-performing loans on the performance of business capital at KSP Kopdit Pelangi Kasih Bandung. This research uses descriptive research method.And.verification with a quantitative approach. The objects in this study were members of the Kopdit Pelangi Kasih Bandung Savings and Loan Cooperative (KSP) with a total sample of 97 people. The sampling technique used in this research is nonprobability sampling method with purposive sampling technique. Statistical analysis of the data used in this study was multiple linear regression analysis using IBM SPSS statistics 24. The results of the study found that members' savings, non-performing loans and working capital performance at KSP Kopdit Pelangi Kasih Bandung were good. There is a significant influence between members' savings and non-performing loans simultaneously on the performance of working capital at KSP Kopdit Pelangi Kasih Bandung. There is a significant influence between member savings partially on the performance of working capital at KSP Kopdit Pelangi Kasih Bandung. Non-performing loans have no significant effect on the performance of working capital at KSP Kopdit Pelangi Kasih Bandung simultaneously. Therefore this can be used by the cooperative as an evaluation material for the performance results so that it can be taken into consideration for making decisions in improving the performance of venture capital in cooperatives. This research is different from other researchers because there are no other researchers who have examined specifically members' savings and problem loans on business capital performance at KSP Kopdit Pelangi Kasih Bandung, besides that indicators of member savings variables have a greater value and influence than problem credit variables